Aesthetic Improvement of Undeveloped Calves After Treatment of Congenital Clubfoot Deformity. (21st February 2018) - Andjelkov, Katarina; Llull, Ramon; Colic, Milan; Atanasijevic, Tatjana C; Popovic, Vesna M; Colic, Miodrag
Abstract: Background: Even when clubfoot deformity is treated in a timely manner, the consequences observed in adulthood include hypoplasia of the calf muscles, gait impairment, decreases in foot size, and it can also affect the tibial length. These consequences may have negative impacts on the patient's subjective appraisal of long-term outcomes, and can influence the patient's self-esteem in both male and female patients. Objectives: We present our experience in the treatment of undeveloped calves after surgical treatment of congenital clubfoot. Methods: In total, 72 patients underwent corrective surgery in order to improve undeveloped calves resulting from a congenital clubfoot deformity. We used calf silicone implants in combination with fat grafting in multistaged procedures, in order to decrease complication rates and improve aesthetic outcome. Results: Amongst our patients there were 54 (75%) females and 18 (25%) males. All of the patients, except one, had unilateral calf hypoplasia. The procedures were divided into several groups: (1) medial calf augmentation with silicone implants; (2) medial calf augmentation with silicone implants and fat grafting; and (3) medial and lateral calf augmentation with silicone implants and fat grafting. We had one case of a hyperpigmented scar and one case of partial scar dehiscence. There were no cases of compartment syndrome. The average follow-up period was 9.8 months. Conclusions: Calf enhancement surgery in patients with congenital clubfoot deformity is very gratifying. When combining calf implants with fat grafting in multistaged procedures, we can achieve excellent results with low complication rates. Level of Evidence: 4: